Establishment of callus and cell suspension culture of Sophora alopecuroides Linn. for the production of oxymatrine - Tsolmon, M.; Oyundari, G; Yu, Oyunbileg; Senthil, Kalaiselvi (Journal of Phytology, 2020)
Oxymatrine is one of the most important biologically active compounds and is present in Sophora alopecuroides L. The present investigation focuses on the development of an efficient tissue culture method to induce callus and cell suspension culture of S. alopecuroides by studying the effect of jasmonic acid and nitric oxide on cell suspension culture. Callus induction efficiency is high in axenic leaf explants grown in MS medium supplemented with 1.0 mg/L Kinetin (Kin), 1.0 mg/L 2,4-dichlorophenoxyacetic acid (2,4-D). The cell suspension culture was developed using the same callus induction medium without agar. The maximum cell number and dry weight of suspension culture were obtained by the 9th day of incubation. The synthesis of oxymatrine is higher in jasmonic acid and nitric oxide (200 µMJA and 50 µMNO) combination (11.91 µg/g) when compared to the non-elicited control (8.3 µg/g) of callus.